The Abbasids and the Architectural Development of the Prophet’s Mosque: the Consequences of a Political Disintegration - Spahic, Omer (Bursa İlahiyat Foundation, Hacılar Mh. Eceler Sk. Sema Apt. No: 6/5, Osmangazi, Bursa-Turke, 2016)
This article discusses the contributions of the Abbasid caliphs to the architectural development of the Prophet’s Mosque in Madinah. Those contributions began almost as early as the Abbasid caliphal government had officially emerged as the successor to the Umayyads, and ended with a major rebuilding and renovation work in 887 AH/1482 CE, about 35 years before the ultimate dissolution of the Abbasid regime. The last work was executed by the Mamluk rulers as the Abbasid proxies. That was so because following the fall of Baghdad in 656 AH/1258 CE, the Abbasids moved to Egypt where, under the patronage of the powerful Mamluk dynasty, they maintained only a feeble show of authority, confined to religious matters. Henceforth, their caliphate became but ceremonial and titular. Since the protracted Abbasid rule went through several precarious phases, it was frequently marred by acute religious and socio-political disorders and turbulences, so much so that its mere existence was occasionally threatened. The history and architectural development of the Prophet’s Mosque was not immune to such conditions. Its architectural integrity and predisposition, and overall functioning as a community development center, were now and then at risk. Thus, this article focuses on discussing the consequences and implications of a political disintegration during the Abbasid era for the architectural development and serviceability of the Mosque. The article concludes that the Abbasid contributions to the architectural development of the Mosque was rather inadequate. The blame is to be attributed partly to the Abbasids themselves and partly to the prevalent circumstances in the state that eventually incapacitated the Abbasid government from performing its entrusted duties and responsibilities. However, even for the creation and fostering of the latter, it was again the Abbasids who more than anybody else are to be held accountable.